2020
DOI: 10.3389/fneur.2020.00614
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Tramiprosate (Homotaurine) in Alzheimer's Disease and Other Neurocognitive Disorders

Abstract: Alzheimer's disease (AD) is the most prevalent neurodegenerative condition, especially among elderly people. The presence of cortical β-amyloid deposition, together with tau phosphorylation and intracellular accumulation of neurofibrillary tangles (NFT) is the main neuropathologic criteria for AD diagnosis. Additionally, a role of inflammatory, mitochondrial, and metabolic factors has been suggested. Tramiprosate binds to soluble amyloid, thus inhibiting its aggregation in the brain. It reduced oligomeric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 79 publications
(106 reference statements)
1
38
0
Order By: Relevance
“…The amyloid-β oligomers are believed to be a key pathogenic driver in the disease process. The homotaurine mechanism prevents the self-assembly of misfolded proteins into amyloid-β oligomers that leads to amyloid aggregation and subsequently causes neurotoxicity and clinical progression of AD [ 137 ]. This genetic knowledge emerged after phase III clinical studies of tramiprosate in AD patients and prompted a precision medicine approach and analysis of the genetically defined subset of AD patients in homotaurine studies.…”
Section: Marine Compounds Against Alzheimer’s Disease: From Sea To Cellsmentioning
confidence: 99%
“…The amyloid-β oligomers are believed to be a key pathogenic driver in the disease process. The homotaurine mechanism prevents the self-assembly of misfolded proteins into amyloid-β oligomers that leads to amyloid aggregation and subsequently causes neurotoxicity and clinical progression of AD [ 137 ]. This genetic knowledge emerged after phase III clinical studies of tramiprosate in AD patients and prompted a precision medicine approach and analysis of the genetically defined subset of AD patients in homotaurine studies.…”
Section: Marine Compounds Against Alzheimer’s Disease: From Sea To Cellsmentioning
confidence: 99%
“…Studies on model mice showed that long-term administration of carnosine affected the suppression of the accumulation of senile plaques [ 27 ], and it also had protective and anti-inflammatory effects on brain cells [ 28 ]. A similar low-molecular-weight prodrug is a homotaurine [ 101 ]. Homotaurine was also shown to eliminate senile plaques and to have pharmacokinetics that could pass through the BBB, and a large-scale phase 3 study was conducted in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Potent inhibitors of the formation of Abeta fibrils or plaques are therapeutic antibodies, as described below. A small molecule that blocks the formation of Abeta dimers is homotaurine (tramiprosate) [ 83 ], which is a highly polar molecule, 3-amino-1-propanesulfonic acid, that, in the absence of carrier mediated transport, would be expected to have minimal BBB transport. A clinical trial of homotaurine for AD did not result in an improvement in cognitive decline [ 84 ].…”
Section: Small Molecule Drugs For Alzheimer’s Diseasementioning
confidence: 99%